Effects of growth hormone on glucose metabolism and insulin resistance in human - Shin-Hye Kim; Mi-Jung Park (Korean Society of Pediatric Endocrinology, 2017)
Growth hormone (GH) is important for promotion of somatic growth and the regulation of substrate metabolism. Metabolic action of GH occurs in multiple tissues including the liver, muscle, fat and pancreas either directly or indirectly through insulin-like growth factor 1. The diabetogenic action of GH has been well-described in previous in vivo studies. In this paper, we review the metabolic effects of GH on peripheral tissues focusing on glucose metabolism and insulin resistance, and discuss results from human studies on the long-term effects of GH administration on insulin resistance and hyperglycemia.